Loss of the Fbw7 tumor suppressor rewires cholesterol metabolism in cancer cells leading to activation of the PI3K-AKT signalling axis - Bengoechea-Alonso, Maria T.; Aldaalis, Arwa; Ericsson, Johan (Frontiers in Oncology, 2022)
The sterol regulatory-element binding proteins (SREBPs) are transcription factors controlling cholesterol and fatty acid synthesis and metabolism. There are three SREBP proteins, SREBP1a, SREBP1c and SREBP2, with SREBP1a being the strongest transcription factor. The expression of SREBP1a is restricted to rapidly proliferating cells, including cancer cells. The SREBP proteins are translated as large, inactive precursors bound to the endoplasmic reticulum (ER) membranes. These precursors undergo a two-step cleavage process that releases the amino terminal domains of the proteins, which translocate to the nucleus and function as transcription factors. The nuclear forms of the SREBPs are rapidly degraded by the ubiquitin-proteasome system in a manner dependent on the Fbw7 ubiquitin ligase. Consequently, inactivation of Fbw7 results in the stabilization of active SREBP1 and SREBP2 and enhanced expression of target genes. We report that the inactivation of Fbw7 in cancer cells blocks the proteolytic maturation of SREBP2. The same is true in cells expressing a cancer-specific loss-of-function Fbw7 protein. Interestingly, the activation of SREBP2 is restored in response to cholesterol depletion, suggesting that Fbw7-deficient cells accumulate cholesterol. Importantly, inactivation of SREBP1 in Fbw7-deficient cells also restores the cholesterol-dependent regulation of SREBP2, suggesting that the stabilization of active SREBP1 molecules could be responsible for the blunted activation of SREBP2 in Fbw7-deficient cancer cells. We suggest that this could be an important negative feedback loop in cancer cells with Fbw7 loss-of-function mutations to protect these cells from the accumulation of toxic levels of cholesterol and/or cholesterol metabolites. Surprisingly, we also found that the inactivation of Fbw7 resulted in the activation of AKT. Importantly, we found that the activation of AKT was dependent on SREBP1 and on the accumulation of cholesterol. Thus, we suggest that the loss of Fbw7 rewires lipid metabolism in cancer cells to support cell proliferation and survival.